Kecenderungan melakukan agresivitas verbal pada remaja perempuan: Menguji peranan kontrol diri - Gerce Nura Natingkaseh; Adnani Budi Utami; Hetti Sari Ramadhani (INNER: Journal of Psychological Research, 2022)
Abstract Verbal aggression is behavior that hurts others by reproaching or swearing, swearing, ridicule and threats through words. This is often done by teenage girls due to lack of attention from family, feeling depressed, bad associations and not closing the possibility of watching violent shows on social media. It is suspected that a person's aggressive behavior is influenced by his self-control (Krahe, 2013). Self-control is a person's ability to change and direct his behavior in a positive direction in the face of existing stimuli. This study was conducted to determine the relationship between self-control and the tendency to perform verbal aggressiveness in adolescent girls. This study was conducted on 104 adolescent girls in Kaimana Regency, West Papua. The sampling technique in this study was convenience sampling. The sample in this study were female adolescents aged 15-19 years. The rxy value is negative, meaning that the higher the self-control, the lower the tendency for verbal aggressiveness. Keywords: Adolescent Girls; Self-Control; Tendency of Verbal Aggressiveness.